Digital transformation of healthcare system with IoT - Ramana, B. V.; Kumar, B. R. Sarath (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Now a days, internet of things (IoT) is unique and modern, the capability to change the manner in which medicinal services is conveyed. There are no usual denotations for the IoT, according to the sense of Gartner, Internet of Things, is a network of bodily objects that comprise embedded technology to communicate and interact with their internal states or the external environment. The classification expresses that IoT is a unique universal system framework with self-designing capabilities dependent on communication conventions where practical things have characters, physical features, and simulated characters and use savvy interfaces, and are flawlessly incorporated into the data organize. It is possible to monitor patient history whenever and where ever required from anyplace by the specialist. These datasets are used to know the patient’s antiquity and consequent analysis would be done by using machine learning algorithms. These datasets analyzed by using naive bayesian algorithm.